Analisis Rantai Nilai Komoditas Cabai Rawit di Kecamatan Bulawa Kabupaten Bone Bolango - Sri Fatmawati Isini; Ria Indriani; Echan Adam (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
This study aims to analyze the value chain of cayenne pepper in Bulawa District and analyze the added value of marketing among value chain actors in Bulawa District, Bone Bolango Regency. The research method used to determine the sample of farmers is using the purposive sampling method while for the sample of traders using the snowball sampling method. . Respondents in this study were cayenne pepper farmers from selected villages in Bulawa District, namely 18 farmers in Mamungaa Village and 20 farmers in East Mamungaa Village. As for the respondents, there are 8 traders consisting of 1 wholesaler, 2 collectors, and 5 retailers. The data that has been collected is then analyzed using value chain analysis based on Porter's theory and value added marketing analysis. The results show that there are 6 stages of the value chain, starting from purchasing inputs for production facilities, cultivation, harvesting, processing and distribution to consumers. At the cayenne pepper value chain stage in Bulawa District, 4 main actors are involved, namely farmers, wholesalers, collectors and retailers. The value chain of cayenne pepper in Bulawa District is divided into two activities, namely main activities and supporting activities. In the main activity, farmers and traders have a good cooperative relationship and are not dependent even though they are not well organized in terms of price and also cayenne pepper production. In supporting activities, each chain actor has not developed and innovated technology to support the business. The cayenne pepper value chain flow is efficient, but the activities carried out are still simple. The marketing value added and the largest value added ratio are obtained by central market retailers because central market retailers take a larger marketing margin than other traders by minimizing the marketing costs incurred.